1985
DOI: 10.1073/pnas.82.11.3606
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones increase Na+-H+ exchange activity in renal brush border membranes.

Abstract: Na+-H' exchange activity, i.e., amiloridesensitive Na' and H' flux, in renal proximal tubule brush border (luminal) membrane vesicles was increased in the hyperthyroid rat and decreased in the hypothyroid rat, relative to the euthyroid animal. A positive correlation was found between Na'-H' exchange activity and serum concentrations of thyroxine (T4) and triiodothyronine (T3). The thyroid status of the animal did not alter amiloride-insensitive Na' uptake.The rate of passive pH gradient dissipation was higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(49 citation statements)
references
References 27 publications
7
42
0
Order By: Relevance
“…The thyroid hormone status was found to have a greater impact on Na + /H + antiporter activity in adult rats than we found in our neonatal rats (8,28). In agreement with our study, NHE3 mRNA abundance was comparable in both hypothyroid and euthyroid adult rats and was higher in hyperthyroid rats (3).…”
Section: Discussionsupporting
confidence: 91%
“…The thyroid hormone status was found to have a greater impact on Na + /H + antiporter activity in adult rats than we found in our neonatal rats (8,28). In agreement with our study, NHE3 mRNA abundance was comparable in both hypothyroid and euthyroid adult rats and was higher in hyperthyroid rats (3).…”
Section: Discussionsupporting
confidence: 91%
“…At equilibrium (180 min), accumulation of 22Na was, however, similar in control and diabetic vesicles. As previously discussed (35,36), the latter finding indicates that diabetes did not influence average intravesicular volume and, therefore, the increased 22Na uptake at early time points (up to 3 min) could not be ascribed to altered vesicular size in these experiments. Since similar aliquots of membrane proteins were used in the transport experiments, this also rules out changes in vesicular number as being responsible for increased 22Na uptake observed in these experiments.…”
Section: Resultssupporting
confidence: 80%
“…While studies in rabbit brush border membrane vesicles have found that the Na/H antiporter is very sensitive to amiloride (25,26), similar studies in rat brush border vesicles have found less sensitivity to amiloride (31,32). Based on the data of Kinsella and Sacktor (31), and of Sabolic and Burckhardt (32) in rat brush border membrane vesicles, one would predict that 2 mM amiloride in the presence of 75 meq/liter Na would inhibit Na/H exchange by 81% and 67%, respectively. These predictions are relatively similar to our finding that the rate of pH change after luminal sodium removal was inhibited by 81% by 2 mM amiloride.…”
Section: Discussionmentioning
confidence: 97%